Plotters and Martyrs: The Justice and Development Party's (AKP) Constituting of Political Actors in the 15 July Coup Event. (2nd October 2018) - Houston, Christopher
ABSTRACT: In 2016 an unexpected and ill-organized coup d'état occurred in Turkey. It failed within 24 hours, in part due to the bravery of thousands of citizens who in opposition to the soldiers and tanks occupied the squares and streets of Istanbul and Ankara. Designated in the political vernacular as the 15 July event, the AKP government has sought to compose its authorized version of the coup attempt through urban ritual and performance, even as it governs using repressive state of emergency decrees. This paper describes and assesses the reception of this symbolic and narrative work, which is intended to foster in citizens certain desired affective feelings and understandings about the coup attempt. It concludes that the government's symbolic offensive has been a relative failure in modifying the perceptions of Istanbul's inhabitants. This failure relates to citizens' experiential knowledge of the government's less-than-democratic previous acts in Istanbul, most significantly in its violent response to the mass Gezi Park protests in 2013. Equally importantly, it also reveals the importance of the temporal layering of experience for political perception, and thus of the significance of political subjects' historical being.